Introduction to management science - Taylor, Bernard W. (Pearson, 2017)
Using simple, straightforward examples to present complex mathematical concepts, Introduction to Management Science gives students a strong foundation in how to logically approach decision-making problems. Sample problems are used liberally throughout the text to facilitate the learning process and demonstrate different quantitative techniques. Management Science presents modelling techniques that are used extensively in the business world and provides a useful framework for problem-solving that students can apply in the workplace.